Generation of Electricity from Whey: An Electrochemical Process - Sreejon, Das; Yousuf, Abu; Md. Nasir, Uddin; Khan, Maksudur R.; Ahmed Nazmus, Sakib (ijrer.org, 2014)
This study is concentrated on the electricity generation from whey over and done with a fabricated electrochemical cell. Whey (milk serum) is one of the prominent sources of bio-electrolyte because of containing abundant amount of branched-chain amino acids. It is one of the non-useable by-products in the sweetmeat company and also harmful for our environmental pollution in case of open dumping. We choose whey because of its low pH content about 3.1-3.3. Moreover, the utilization of this kind of waste material can be important raw materials for power generation. Two categories of preservation techniques have been revealed by thermal treatment and adding 2% phenol by volume. It was observed that phenol treated whey was free form microbial attack for longer time compared to that of thermal treatment. The measurement of voltage and power density is important to estimate the efficiency and competency of the system. In agitation assisted bio-electrochemical reactor, voltage and power density were increased with the increase of electrode surface area. Maximum 17.35 volt was obtained from 6.5 litres of whey through an agitation assisted electrochemical reactor. In addition, commercial alloy electrode shows satisfactory results on power generation and reducing internal resistance compares with the experimental pure metal electrode. This technology has implication on the recovery of the power crisis in rural and remote areas where the national electricity supply is inaccessible. This approach is also convenient for portable use of electricity in household purposes.